(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
With the development of the theory of virtual reality, three-dimensional virtual human is being applied in clothing engineering design. Parameterized model for virtual human body hence becomes more and more important. In this paper, a parameterized model for virtual human body was reported. In this model, the virtual human body was partitioned into several parts (head, right arm, left arm, trunk, right leg, and left leg). Based on the partitioned human model, the proportional characteristics of the human body were used to calculate the offset of the vertices to implement the deformation on specific part of the body. The interpolation method was used to smoothen the deformed surfaces. The experimental results show that this method had good deformation effect.